Star Wars, Dawn of the Jedi. Book 02, Prisoner of Bogan - Ostrander, John (Star wars: dawn of the Jedi, 2013)
"When Xesh, a mysterious warrior, becomes enthralled with a mad Je'daii obsessed with conquering known space, Je'daii teams are dispatched to stop the mad Je'daii and save the misguided Xesh"--Provided by publisher.